Urban Sprawl Mapping For Cultural Tourism Suitability Using GIS-AHP Model In Kuantan District - Shahrul Marwan, Mohd Hamdan (2023)
It is vital to choose suitable sites for culturally linked activities that take place inside urban settings. This is because both the growth of urban areas and the demand for cultural tourism have risen in recent years. To be successful in reaching this objective, you will need tools that are both efficient in terms of planning and decision-making. When analyzing and mapping the potential for cultural tourism activities in urban zones, this research recommends utilizing a Geographic Information System (GIS) in combination with the Analytic Hierarchy Process (AHP). In order to create this model, the data obtained from Geographic Information Systems (GIS) were coupled with the AHP approach. This is done in order to provide the model the ability to make accurate predictions about which locations have the most potential for the growth of cultural tourism. The model takes into consideration a broad range of factors, some of which include, to mention a few examples, the quality of the environment, accessibility, patterns of land use, and transportation infrastructure. The AHP gives relative importance ratings for each component, and the GIS makes it feasible to undertake geographical research and publish the findings of that study. Together, these two tools make up the analytical framework known as the analytic hierarchy process. This strategy makes resource allocation simpler and contributes to the enhancement of tourism based on cultural events by providing crucial information that can be used by city planners and developers. The idea that has been presented has the potential to assist with a number of different things, such as making cities a more attractive place to live, contributing to the economy, making people happy, and protecting the environment from harm.